The Involvement of Microglial Cells in Japanese Encephalitis Infections. (7th August 2012) - Thongtan, Thananya; Thepparit, Chutima; Smith, Duncan R.
Abstract : Despite the availability of effective vaccines, Japanese encephalitis virus (JEV) infections remain a leading cause of encephalitis in many Asian countries. The virus is transmitted to humans by Culex mosquitoes, and, while the majority of human infections are asymptomatic, up to 30% of JE cases admitted to hospital die and 50% of the survivors suffer from neurological sequelae. Microglia are brain-resident macrophages that play key roles in both the innate and adaptive immune responses in the CNS and are thus of importance in determining the pathology of encephalitis as a result of JEV infection.